2018
DOI: 10.3389/fmicb.2018.01919
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Insights Into the Growth Phase- and Sugar-Associated Changes in the Exopolysaccharide Production of a High EPS-Producing Streptococcus thermophilus ASCC 1275

Abstract: In a previous study, incorporation of high exopolysaccharide (EPS) producing dairy starter bacterium Streptococcus thermophilus ASCC 1275 was found to improve functionality of low fat mozzarella cheese and yogurt. This bacterium in its eps gene cluster has a unique pair of chain length determining genes, epsC- epsD, when compared to other sequenced S. thermophilus strains. Hence, the aim of this study was to understand the regulatory mechanism of EPS production in this bacterium using transcriptomic analysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
38
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 69 publications
5
38
0
Order By: Relevance
“…The whole genome sequencing of S. thermophilus 1275 revealed that it has a unique set of chain length determining genes in its EPS gene cluster when compared with the other five fully sequenced S. thermophilus strains 10 . We have also observed that the sugar available in the media and growth phase influence the amount of EPS produced by S. thermophilus 1275 and the genes that lead to the production of EPS 13 . Another interesting feature of S. thermophilus 1275 is the presence of an effective proteolytic system with several intracellular peptidases and proteases 10 .…”
mentioning
confidence: 72%
See 4 more Smart Citations
“…The whole genome sequencing of S. thermophilus 1275 revealed that it has a unique set of chain length determining genes in its EPS gene cluster when compared with the other five fully sequenced S. thermophilus strains 10 . We have also observed that the sugar available in the media and growth phase influence the amount of EPS produced by S. thermophilus 1275 and the genes that lead to the production of EPS 13 . Another interesting feature of S. thermophilus 1275 is the presence of an effective proteolytic system with several intracellular peptidases and proteases 10 .…”
mentioning
confidence: 72%
“…S. thermophilus 1275 was found to produce high amount of EPS in 1% sucrose supplemented medium when compared to lactose and glucose 13 . Hence, in this study, we investigated the proteome of high EPS producing dairy bacterium S. thermophilus 1275 and compared the proteomic level differences in this bacterium under the influence of three sugars, glucose, sucrose and lactose at two growth phases 5 h and 10 h. This is the first study providing insight into the proteomics of a high EPS producing lactic acid bacterium.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations